Answer:
f(x) = 2 - 10 (1 + x) + 12 (1 + x)^2 - 4 (1 + x)^3
Explanation:
The general form of the series is shown in the attachment. For the purpose here, we need to evaluate f(-1), f'(-1), f''(-1) and so on.
f(x) = 2x -4x^3; f(-1) = 2(-1)(1 -2(-1)^2) = (-2)(-1) = 2
f'(x) = 2 -12x^2; f'(-1) = 2 -12(-1)^2 = -10
f''(x) = -24x; f''(-1) = -24(-1) = 24
f'''(x) = -24; f'''(-1) = -24
So, the series is ...
f(x) = 2 -10(x +1)/1! +24(x +1)^2/2! -24(x +1)^3/3!
f(x) = 2 -10(x +1) +12(x +1)^2 -4(x +1)^3 . . . . . . . matches the first choice